Evolution of the Permo‐Triassic Satpura Gondwana Basin, Madhya Pradesh, India: Insights from geochemical provenance and palaeoclimate of the siliciclastic sediments. Issue 2 (19th October 2022) - Singh, Yumlembam Priyananda; Kingson, Oinam; Sharma, Kongrailatpam Milankumar; Ghosh, Prosenjit; Patnaik, Rajeev; Tiwari, Raghavendra Prasad; Pattanaik, Jitendra Kumar; Kumar, Pankaj; Thomas, Harel; Singh, Ningthoujam Premjit; Singh, Nongmaithem Amardas
Abstract : Geochemical study in the siliciclastic sediments of a basin provides an understanding of palaeoclimate, provenance and subsequently, it can be used to reconstruct the palaeo‐tectonics and evolution of the basin. Sedimentation in the Gondwana basins, worldwide, generally provides a record of climatic fluctuations and evidences of the Permo‐Triassic mass extinction. In spite of its global importance, our knowledge about the nature of sedimentation, basin development and conceptual regional tectonic model in the Satpura Basin, one of the Gondwana basins of India is limited. Major and trace element concentrations of the mudstones from the Denwa Formation along with the existing geochemical data of other formations are studied here for establishing a comprehensive idea about the palaeoclimate, tectonic settings, provenance and basin evolution. The composition of the sediments in the lowermost Talchir Formation revealed cold and dry climatic conditions at the sources, whereas the sources of the sediments for the overlying formations have experienced warm, humid and semiarid climates. The contributions of the mafic rock‐derived sediments are relatively higher in the Talchir, Barakar and Motur formations compared to the overlying formations. Approximately 60% of the sediments in the overlying Bijori, Pachmarhi and Denwa formations were derived from the felsic volcanic rocks and granites of the Sausar Mobile Belt and Betul‐Chindwara Mobile Belt (BCMB) with minor inputs from mafic volcanic rocks of the BCMB. Furthermore, the sediments of the Talchir Formation were derived from the BCMB when they became tectonically active, whereas the sediments in the younger formations have been derived from a passive tectonic setting. Abstract : The sediment of Satpura Basin reflects the transition of climate between the global ice‐house to the greenhouse during the Permo‐Triassic period. The sediments are mostly derived from the SMB and BCMB belts. The felsic rocks dominantly contributed to the sediments of the Satpura Basin with subordinate mafic rocks.